2018
DOI: 10.1038/s41467-018-05806-0
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-IV binds αIIbβ3 integrin and inhibits thrombosis

Abstract: Platelet αIIbβ3 integrin and its ligands are essential for thrombosis and hemostasis, and play key roles in myocardial infarction and stroke. Here we show that apolipoprotein A-IV (apoA-IV) can be isolated from human blood plasma using platelet β3 integrin-coated beads. Binding of apoA-IV to platelets requires activation of αIIbβ3 integrin, and the direct apoA-IV-αIIbβ3 interaction can be detected using a single-molecule Biomembrane Force Probe. We identify that aspartic acids 5 and 13 at the N-terminus of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 71 publications
1
73
0
1
Order By: Relevance
“…However, only three strains, namely Plank-SS-01, Lepto-CH and Osci-NB-01, contained a high percentage of oleic acid (25%, 28%, and 27%, respectively). Several studies on this monounsaturated acid have demonstrated its powerful antioxidant effect (Ceron et al, 2007) and its anti-platelets aggregation property (Xu et al, 2018), the acid thus presenting a promising potential as an accessible and safe alternative to synthetic molecules. In addition, Harada et al (2000) demonstrated the larvicidal activity of this fatty acid extracted from P. agardhii, especially against mosquito larvae.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…However, only three strains, namely Plank-SS-01, Lepto-CH and Osci-NB-01, contained a high percentage of oleic acid (25%, 28%, and 27%, respectively). Several studies on this monounsaturated acid have demonstrated its powerful antioxidant effect (Ceron et al, 2007) and its anti-platelets aggregation property (Xu et al, 2018), the acid thus presenting a promising potential as an accessible and safe alternative to synthetic molecules. In addition, Harada et al (2000) demonstrated the larvicidal activity of this fatty acid extracted from P. agardhii, especially against mosquito larvae.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Whole blood was incubated with testing reagents for 15 minutes at 37°C, and then perfused over immobilized collagen (100 μg/mL, overnight at 4°C) at flow rates that generated wall shear stresses of 5, 20 and 100 dynes/cm 2 for 5 minutes at room temperature in a microfluidic chamber (Cellix Mirus Nanopump), according to a previously established protocol . The chamber was then washed with phosphate‐buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of coagulation-related indicators, most scientists believe that inflammation can stimulate the vascular endothelium to activate platelets and promote the binding of platelets to fibrinogen, thereby promoting arteriosclerotic thrombosis. Our previous study revealed that apolipoprotein A-IV is a new ligand for platelet GPIIβ/IIIα integrin, which competitively inhibits the binding of glycoprotein GPIIβ/IIIα to fibrinogen and inhibits platelet aggregation [25,27]. In this study, platelet function will be used as an entry point to explore whether acupuncture can antagonize the binding of platelets to fibrinogen by changing the level of apolipoprotein A-IV, thereby reducing the PAR in blood and reducing the formation of plaque.…”
Section: Comprehensive Selection Of Outcome Measuresmentioning
confidence: 99%